Financial development and bioenergy consumption in the EU28 region: evidence from panel auto-regressive distributed lag bound approach - Alsaleh, Mohammed; Abdul Samad @ Iammi, Abdul Rahim (MDPI, 2019)
This paper investigates the relationship between financial development and bio-energy consumption in the European Union (EU28) countries for the period from 1990 to 2013 through the panel autoregressive distributed lag (ARDL) approach and causality analysis. The empirical results show that financial development shows a significant positive impact, at a 1% statistical level, on bio-energy consumption for the EU28 during the studied period. In developing countries, the financial market indicator affects bio-energy consumption outgrowth positively and significantly at a 1% statistical level. For developed countries, there is a positive influence of financial institutions and financial market indicators on bio-energy consumption growth at the 1% and 10% levels, respectively. The study concludes that there is a significant relationship between the consumption of bio-energy and financial development factors. The study provides recommendations that are useful when formulating policy related to energy consumption and the promotion of bio-energy consumption. Financial development and economic outgrowth show a significant influence on the outgrowth of bio-energy consumption at a 1% statistical level.